Simple Bookkeeping Training for Weaving Business Groups on the Toloweri Neighborhood in Bima City - Puji Muniarty; Nurhayati Nurhayati; Aliah Pratiwi (Indonesian Journal of Social Sciences and Humanities, 2020)
Fabric woven products are one of the results of local wisdom that is characteristic and pride that is in demand by people outside Bima City, West Nusa Tenggara. There is no set price standardization, the form of financial statements that have not been detailed, limitations of human resource knowledge in the management of financial and institutional MSMEs have not been formed so that it attracts the attention of the writer to conduct simple bookkeeping training services for weaving business groups in Toloweri Environment, Nungga Sub-District, East Rasanae District, Bima City. The stages of the method of implementing simple bookkeeping training are (1) the planning stage, (2) the implementation phase and (3) the evaluation phase. The results achieved from this activity are the management of the weaving business group knowing how to prepare financial statements to calculate the profit or loss of the business. The conclusion is that in general no significant obstacles were found but a positive response was reflected in the enthusiasm of the participants involved in this simple bookkeeping training which was very helpful in the implementation of the service.